I want to know how to integrate this function I have tried many things many substitutions but none works.

I even try to expand the numerator by $\sin3x$ and $\cos3x$ properties and tried to convert higher powers to multiple angles


3 Answers 3


$$ \int \frac{\sin {3x} + \cos{3x}}{ \sin^3 x + \cos^3 x } dx\ =\int \frac{3\sin x -4\sin^3x+4\cos^3x-3\cos x}{ \sin^3 x + \cos^3 x } dx=\int \frac{(\cos x -\sin x)(1+ 4\sin x \cos x)}{ (\sin x + \cos x)(1- \sin x\cos x) } dx=\int \frac{(\cos^2 x -\sin^2 x)(1+ 4\sin x \cos x)}{ (\sin x + \cos x)^2(1- \sin x\cos x) } dx=\int \frac{\cos 2x (1+ 2\sin 2x)}{ (1+ \sin 2x)(1- 0.5\sin 2x) } dx=0.5\int \frac{1+ 2\sin 2x}{ (1+ \sin 2x)(1- 0.5\sin 2x) } d(\sin 2x)$$ Hope you can finish from here.

  • $\begingroup$ How does $3\sin x - 4\sin^3 x+4\cos^3 x- 3\cos x$ become $(\cos x -\sin x)(1+\sin x\cos x)$? Shouldn't it be $(\cos x -\sin x)(1+4\sin x\cos x)$? $\endgroup$
    – GoodDeeds
    Sep 4, 2018 at 20:11
  • $\begingroup$ @GoodDeeds: Thank you for spotting my mistake $3(\sin x-\cos x)-4(\sin x-\cos x)(1+\sin x \cos x)=(\sin x - \cos x)(3-4(1+\sin x \cos x))=(\sin x - \cos x)(3-4-4\sin x \cos x)=(\cos x - \sin x)(1+ 4\sin x\cos x)$ $\endgroup$
    – Vasili
    Sep 4, 2018 at 20:25

Use \begin{equation}\cos\left(3x\right)=\cos^3\left(x\right)-3\cos\left(x\right)\sin^2\left(x\right) \end{equation} and \begin{equation} \sin\left(3x\right)=3\cos^2\left(x\right)\sin\left(x\right)-\sin^3\left(x\right) \end{equation} accompanied with \begin{align} \sin\left(x\right)&=\dfrac{\tan\left(x\right)}{\sec\left(x\right)} \\ \cos\left(x\right)&=\dfrac{1}{\sec\left(x\right)} \\ \sec^2\left(x\right)&=\tan^2\left(x\right)+1 \end{align} You will get \begin{equation} {\int}{{\sec^2\left(x\right)}}{{\left(-\dfrac{\tan^3\left(x\right)+3\tan^2\left(x\right)-3\tan\left(x\right)-1}{\tan^5\left(x\right)+\tan^3\left(x\right)+\tan^2\left(x\right)+1}\right)}}\,\mathrm{d}x \end{equation} Use the change of variable $u = \tan (x)$ then $dx = \frac{1}{\sec^2 (x)} du$, you will get \begin{equation} {\int}\dfrac{u^3+3u^2-3u-1}{u^5+u^3+u^2+1}\,\mathrm{d}u \end{equation} But \begin{equation} {\int}\dfrac{u^3+3u^2-3u-1}{u^5+u^3+u^2+1}\,\mathrm{d}u ={\int}\dfrac{u^3+3u^2-3u-1}{\left(u+1\right)\left(u^2+1\right)\left(u^2-u+1\right)}\,\mathrm{d}u \end{equation} Now perform partial fraction decomposition, we get \begin{equation} {\int}\dfrac{u^3+3u^2-3u-1}{u^5+u^3+u^2+1}\,\mathrm{d}u ={\int}\left(\dfrac{10u-5}{3\left(u^2-u+1\right)}-\dfrac{4u}{u^2+1}+\dfrac{2}{3\left(u+1\right)}\right)\mathrm{d}u \end{equation} That is \begin{equation} {\int}\dfrac{u^3+3u^2-3u-1}{u^5+u^3+u^2+1}\,\mathrm{d}u =\dfrac{5}{3}\underbrace{{}{\int}\dfrac{2u-1}{u^2-u+1}\,\mathrm{d}u}_{\ln \vert u^2-u+1 \vert}- \underbrace{{\int}\dfrac{u}{u^2+1}\,\mathrm{d}u}_{\dfrac{\ln\vert u^2+1\vert}{2}}+ {{\dfrac{2}{3}}} \underbrace{{\int}\dfrac{1}{u+1}\,\mathrm{d}u}_{\ln\vert u+1\vert} \end{equation}

Finally plug back $u = \tan x$.


$$I=\int \frac{\sin {3x} + \cos{3x}}{ \sin^3 x + \cos^3 x } dx=\cdots=\int \frac{(\cos x -\sin x)(1+ 4\sin x \cos x)}{ (\sin x + \cos x)(1- \sin x\cos x) } dx$$

As $\dfrac{d(\sin x+\cos x)}{dx}=\cos x-\sin x$

if we choose $\sin x+\cos x=u, 2\sin x\cos x=u^2-1$


Now use Partial Fraction Decomposition, $$\dfrac{2u^2-1}{u(3-u^2)}=\dfrac Au+\dfrac{Bu+C}{3-u^2}$$



Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.